Diagnostic Accuracy of Charge-coupled Device Sensor and Photostimulable Phosphor Plate Receptor in the Detection of External Root Resorption In Vitro - Shirin Sakhdari; Zohreh Khalilak; Elham Najafi; Rezvaneh Cheraghi (Tabriz University of Medical Sciences, 2015)
Background and aims. Early diagnosis of external root resorption is important for accurate treatment. The purpose of this study was to compare the efficacy of a charge-coupled device (CCD) sensor and a photostimulable phosphor (PSP) plate receptor in the diagnosis of artificial external root resorption. Materials and methods. In this diagnostic in-vitro study, 40 maxillary incisors were mounted in a segment of dry bone and preliminary radiographs were obtained using CCD and PSP sensors. Artificial resorption cavities were produced on the middle-third in half of the samples and on the cervical-third in the other half on the buccal root surfaces. Radiographs were repeated and images were evaluated. Data were statistically analyzed using chi-square and diagnostic tests. Results. There were no significant differences between the two sensors in the sensitivity (p=0.08 and 0.06) and specificity (p=0.13) for the diagnosis of resorption in both root areas. The overall accuracy of CCD was higher than PSP sensor; how-ever, the difference was not statistically significance (p>0.05). Conclusion. CCD and PSP sensors chosen for the present study produced similar results in diagnosing simulated external root resorption.